The Role of E-WOM in Mediating the Influence of Brand Image on Product Purchasing Decisions - Nyoman Sri Manik Parasari; Gusti Ayu Putu Fajar Ayu Cahyanti; Ni Putu Yunita Anggreswari; Anak Agung Istri Agung Maheswari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the context of marketing, e-WOM is a highly influential tool in shaping consumer perceptions and influencing purchasing decisions. This study aims to assess the role of Electronic Word of Mouth (e-WOM) in mediating the influence of brand image on consumer purchasing decisions for Voordurend Love, a local fashion brand in Bali. This research employs a quantitative method, utilizing an online questionnaire distributed to 130 respondents from Generation Z and Millennials who are familiar with and have purchased Voordurend Love products. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) Version 4. The findings reveal that brand image has a significant positive effect on e-WOM and purchasing decisions. Additionally, e-WOM positively influences purchasing decisions. One key finding is that e-WOM serves as a mediating variable, strengthening the impact of brand image on purchasing decisions. This study underscores the importance of maintaining a strong brand image and proactively managing online consumer reviews to enhance purchase intentions in the digital marketplace.